Genomic insights into the genetic structure and population history of Mongolians in Liaoning Province - Hou, Xuwei; Zhang, Xianpeng; Li, Xin; Huang, Ting; Li, Wenhui; Zhang, Hailong; Huang, He; Wen, Youfeng (Frontiers in Genetics, 2022)
The Mongolian population exceeds 6 million and has the largest population among the Mongolic speakers in China. However, the genetic structure and admixture history of the Mongolians are still unclear due to the limited number of samples and lower coverage of single nucleotide polymorphism (SNP). In this study, we genotyped genome‐wide data of over 700,000 SNPs in 38 Mongolian individuals from Fuxin in Liaoning province to explore genetic structure and population history based on typical and advanced population genetic analysis methods (principal component analysis (PCA), ADMIXTURE, FST, f3‐statistics, f4‐statistics, qpAdm/qpWave, qpGraph, ALDER and TreeMix). We found that Fuxin Mongolians had close genetic relationship with Han people, northern Mongolians, other Mongolic speakers and Tungusic speakers in East Asia. And we found Neolithic millet farmers in the Yellow River Basin and West Liao River Basin, Neolithic hunter-gatherers in the Mongolian Plateau and Amur River Basin were the dominant ancestral sources, and there were additional gene flows related to Eurasian Steppe pastoralists and Neolithic Iranian farmers in gene pool of Fuxin Mongolians. These results shed light on dynamic demographic history, complex population admixture and multiple sources of genetic diversity in Fuxin Mongolians.